The contributions of Professor Nguyen Van Dao in the Field of Nonlinear Oscillations - Khang, Nguyen Van (Vietnam Journal of Mechanics, 2022)
Nguyen Van Dao is a leading expert in the field of mechanics in Vietnam. In this paper, we present some contributions of Nguyen Van Dao to the theory of nonlinear oscillation. His outstanding studies are the interaction between self-excited, forced and parametric vibrations, and equally important there is the effect of dynamic absorbers in nonlinear systems.